Structural breaks, financial globalization, and financial development: Evidence from Turkey - Pinar Avci; Murat Cetin (Universitas Islam Indonesia, 2022)
Purpose ― Mishkin’s hypothesis suggests that globalization appears to be a vital factor in stimulating the development of the financial system. The study examines this hypothesis for the Turkish economy from 1970 to 2017. It focuses on the link between financial globalization and financial development by integrating economic growth, inflation, and natural resource rent as additional determinants into the financial development specification. Methods ― The Ng-Perron and Vogelsang-Perron unit root tests are used to check the stationarity of variables. The cointegration analysis is performed using the Hatemi-J and ARDL bounds testing procedures. Findings ― The main empirical results show that the series are cointegrated under structural breaks; in the long run, financial globalization and economic growth increase financial development while inflation and natural resource rent negatively affect financial development. A unidirectional causality exists from financial globalization and economic growth to financial development. At the same time, there is bidirectional causality between inflation and financial development, natural resource rent, and financial development. Implications ― The empirical findings can present important recommendations for policymakers. Originality ― Very few time-series studies include Turkey’s economy and structural breaks.